2010
DOI: 10.1021/bi101358k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Bisubstrate Cysteine Desulfurase SufS from Bacillus subtilis

Abstract: Cysteine is the major sulfur donor for thio cofactors in bacterial and eukaryotic systems. The first step in sulfur mobilization involves a PLP-dependent enzymatic mechanism. During catalysis, free cysteine is converted into alanine with the concomitant formation of a persulfide bond with the catalytic cysteine residue, thus forming a covalent enzyme intermediate. Cysteine desulfurases in their persulfurated forms serve as donors at the intersection of various cellular sulfur-requiring pathways. Most Gram-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
94
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(115 citation statements)
references
References 45 publications
16
94
5
Order By: Relevance
“…4, left). The affinity of the enzyme for cysteine (K mCys ϭ 29.7 Ϯ 8.7 M), was similar to the values determined for other cysteine desulfurases (15,23,30). The pH dependence activity profile (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…4, left). The affinity of the enzyme for cysteine (K mCys ϭ 29.7 Ϯ 8.7 M), was similar to the values determined for other cysteine desulfurases (15,23,30). The pH dependence activity profile (Fig.…”
Section: Resultssupporting
confidence: 82%
“…These results provide further support for involvement of the NifZ active-site cysteine in forming a persulfide intermediate during NifZ's catalytic cycle and the occurrence of a persulfide sulfur transfer step from NifZ to ThiI during the biosynthesis of s 4 U8. Recently, we have described the kinetic mechanism of the bisubstrate cysteine-SufU sulfurtransferase reaction catalyzed by the B. subtilis SufS enzyme (23). The presence of the sulfur acceptor SufU increases the catalytic rate of the SufS reaction by Ͼ100-fold.…”
Section: Resultsmentioning
confidence: 99%
“…The affinity of the enzyme for cysteine (K m ϭ 4.3 M) is an order of magnitude greater than that of any other cysteine desulfurase found in B. subtilis (see Fig. S4 in the supplemental material) (17,20). As reported for other cysteine desulfurases, the active-site cysteine (Cys325) is essential for YrvO activity (see Fig.…”
Section: Levels Of Expression Of Mnma Affects Abundance Of Smentioning
confidence: 77%
“…In previous work, we and others showed that sufS is adjacent to its sulfur acceptor gene, sufU (17,18), coding for a zinc-dependent sulfur transfer protein (19). Both proteins are involved in the formation of Fe-S clusters.…”
mentioning
confidence: 99%
“…SufC is an ATPase that has homology with membrane-associated ATPases, SufD participates in Fe acquisition, and SufB is thought to be the site of Fe-S cluster synthesis (12)(13)(14). SufS is a cysteine desulfurase that catalyzes the removal of elemental sulfur from cysteine, producing alanine and a SufS-bound persulfide (15). The persulfide is transferred to SufU, which is a sulfur transfer protein that provides the sulfur to SufBCD (16).…”
mentioning
confidence: 99%